Archiving technologies. Issue 1 (January 2018) - Ketelaar, Eric
Abstract : The Digital Age offers enormous opportunities and poses equally enormous challenges to archiving technologies. Archiving technologies encompass both technologies to archive and the archiving of technologies. These technologies are constructed by people and they facilitate people's actions. Technology is both a product and a medium of human action. The archive is a dynamic process of creation and recreation by "archivers": authors, clerks, registrars, antiquarians, keepers, managers, engineers, website builders, genealogists, family members and indeed, archivists and recordkeeping professionals. Archivers use socially embedded technologies and are constrained by these technologies. This duality shapes the archive but also structures the archiving of technologies. Such archiving is indispensable in a knowledge-based economy, where the level of external and internal knowledge is an important factor determining the costs (and success) of a new technology. However, archiving as a practice of knowledge management in technology industry is not well established, notwithstanding efforts by archivists and historians to raise awareness of the importance of documenting and archiving technologies.